The stick operator: the management of several points of view in a geographical information system. (5th November 2019) - Mondo, Géraldine Del; Mainguenaud, Michel
In this article, we propose the Stick operator which provides a unique point of view from two points of view in the context of a geographical information system. It is based on two alphanumeric data models we merge in order to obtain a single data model (i.e., the result of the Stick operator). This operator uses a set of rules defined on characteristics of data models associated with each point of view. These characteristics are based on the links between the spatial dimension and alphanumeric data. It can be used when two different levels of details/abstraction or two sources have to be merged. We rely on a labelled graph to formalise data models and work till the attribute level. The Stick operator takes advantage of characteristics such as the intersection of graphs, the existence of quasi-strongly connected graphs or paths to provide an extended result data model.